1999
DOI: 10.1093/nar/27.22.4436
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of chemical modification of RNA from formalin-fixed samples and optimization of molecular biology applications for such samples

Abstract: Formalin-fixed archival samples are known to be poor materials for molecular biological applications. We conducted a series of experiments to understand the alterations in RNA in fixed tissue. We found that formalin-fixed tissue was resistant to solubilization by chaotropic agents. However, proteinase K completely solubilized the fixed tissue and enabled the extraction of almost the same amount of RNA as from a fresh sample. The extracted RNA did not show apparent degradation. However, as reported, successful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
479
1
8

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 577 publications
(500 citation statements)
references
References 29 publications
12
479
1
8
Order By: Relevance
“…The use of oligo(dT) priming is a standard labelling approach, but may have contributed to low gene detection rates in FFPET as fragments discontinuous with the poly A tailed region cannot be anchored to oligo(dT) primers. Preferential chemical modification of adenine residues by formalin further compromises the suitability of oligo(dT) for FFPET substrates (Masuda et al, 1999;Paik et al, 2005). A direct comparison of random hexamer and oligo(dT) priming has confirmed that random primers give higher gene detection rates from FFPET (Xiang et al, 2003 launched Nugen and Nugen FFPE protocols utilising both oligo(dT) and random priming are therefore especially promising for FFPET substrates (Nugen Technologies, CA, USA) and are likely to significantly improve the sensitivity of FFPET arrays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of oligo(dT) priming is a standard labelling approach, but may have contributed to low gene detection rates in FFPET as fragments discontinuous with the poly A tailed region cannot be anchored to oligo(dT) primers. Preferential chemical modification of adenine residues by formalin further compromises the suitability of oligo(dT) for FFPET substrates (Masuda et al, 1999;Paik et al, 2005). A direct comparison of random hexamer and oligo(dT) priming has confirmed that random primers give higher gene detection rates from FFPET (Xiang et al, 2003 launched Nugen and Nugen FFPE protocols utilising both oligo(dT) and random priming are therefore especially promising for FFPET substrates (Nugen Technologies, CA, USA) and are likely to significantly improve the sensitivity of FFPET arrays.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, gene detection is likely to improve with the use of newer RNA extraction protocols that have been designed for superior reversal of chemical modifications, albeit that a proportion of these will remain irreversible (Masuda et al, 1999;Paik et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Cumulatively, these lead to suboptimal nucleic acid quality and hampered reverse transcription and amplification reactions. [57][58][59][60] Thus, in the past, gene expression profile studies were restricted to tissues with higher intrinsic nucleic acid quality, such as cell lines, fresh blood or fresh frozen tissue. [61][62][63][64][65][66] Recent biotechnological advances have improved RNA isolation and amplification techniques, resulting in successful use of formalin-fixed paraffinembedded tissues to identify gene signatures in human tumors.…”
Section: Discussionmentioning
confidence: 99%
“…These advances include newer formalin-fixed paraffin-embedded tissue extraction protocols, cDNA-mediated annealing, selection, extension and ligation, the addition of random hexamer priming to oligo(dT) priming and newly developed array platforms with redesigned probes. [30][31][32][33][34]57,[67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82] Although sensitivity is low, high specificity and positive predictive value suggest that transcript detection is reliable from formalin-fixed paraffin-embedded tissue. 33 Although RNA isolation techniques from formalin-fixed paraffin-embedded tissues have improved, problems remain, largely because of the greater fragmented nature of RNA in formalin-fixed paraffin-embedded tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, flow cytometry has been used to sort cells using a spectrum of fluorescent labeling techniques in whicholigonucleotide probes are hybridized to either DNA or RNA target sequences [4][5][6][7] . The principle limitation of these methods has been that RNA extracted from hybridized material is often highly degraded 8,9 . Although fragmented RNA can be reverse transcribed and analyzed by quantitative PCR (RTqPCR) 10,11 , full-length RNA is required for an unbiased representation of the transcriptome.…”
mentioning
confidence: 99%